Smart Responsive Nanoformulation for Targeted Delivery of Active Compounds From Traditional Chinese Medicine - Jiang, Xuejun; Lin, Mei; Huang, Jianwen; Mo, Mulan; Liu, Houhe; Jiang, Yuan; Cai, Xiaowen; Leung, Wingnang; Xu, Chuanshan (Frontiers in Chemistry, 2020)
Traditional Chinese medicine has been used to treat disorders in China for thousand years. Growing evidence has shown that the active ingredients from traditional Chinese medicine have a variety of biological activities, including antibacterial, antiproliferative, antioxidant and apoptosis-inducing features. However, poor solubility and low bioavailability limit clinical applications of active compounds from traditional Chinese medicine. Nanoformulation represents a novel and advanced drug delivery system, showing promising in improving drug solubility and bioavailability. In particular, smart responsive nanoformulations can respond to the specially external and internal stimulus in targeted sites to release the loaded drugs, that endows them to control the release of drug within target tissues. Recent studies have demonstrated that smart responsive nanoformulations achieved the targeted release of active compounds from traditional Chinese medicine at diseased sites to increase their concentrations in diseased tissues and reduce side effects. Herein, we review smart responsive nanoformulations, mainly including internal stimulus-responsive nanoformulations such as pH-, redox- responsive smart nanoformulations, and external stimulus-responsive nanoformulations such as light- and magnetic-responsive nanoformulations, and focus on the application of these smart nanoformulations in active compounds from traditional Chinese medicine against tumor and infectious diseases, to further boost the development of traditional Chinese medicine in modern medicine.